2017
DOI: 10.17507/tpls.0702.03
|View full text |Cite
|
Sign up to set email alerts
|

The Application of Blackboard in the English Courses at Al Jouf University: Perceptions of Students

Abstract: Abstract-The purpose of this study is to investigate the perceptions of students on the use of Blackboard in the Department of English at Al Jouf University. Al Jouf University is located in Al Jouf province in the northwestern part of the Kingdom of Saudi Arabia. A cohort of 50 male students of the university participated in this study. The sample population was selected randomly. The data was collected using a questionnaire. The results of the study suggest that though the students neither agree nor disagree… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 4 publications
1
21
0
2
Order By: Relevance
“…One study that does examine BB learning is the work of Fageeh and Mekheimer (2013) who found that students have positive attitudes towards asynchronous discussion forums; however, they feel more comfortable in conventional face-to-face communication than in asynchronous discussions. Another study by Pusuluri, Mahasneh & Alsayer (2017) focused on the use of BB by EFL learners at Al Jouf University, which is located in Saudi Arabia. Their study revealed that learners appreciate the fact that BB widens the scope of their learning experience.…”
Section: Literature Review Vlles: Merits and Barriersmentioning
confidence: 99%
See 1 more Smart Citation
“…One study that does examine BB learning is the work of Fageeh and Mekheimer (2013) who found that students have positive attitudes towards asynchronous discussion forums; however, they feel more comfortable in conventional face-to-face communication than in asynchronous discussions. Another study by Pusuluri, Mahasneh & Alsayer (2017) focused on the use of BB by EFL learners at Al Jouf University, which is located in Saudi Arabia. Their study revealed that learners appreciate the fact that BB widens the scope of their learning experience.…”
Section: Literature Review Vlles: Merits and Barriersmentioning
confidence: 99%
“…Also, many learners were neutral about BB being considered as an interesting learning environment. Pusuluri et al (2017) associated this neutrality with the learners' insufficient awareness of the benefits of BB. Another study by Ali (2017) has highlighted the positive attitudes of EFL learners towards using BB and related their attitudes to their high motivation levels.…”
Section: Literature Review Vlles: Merits and Barriersmentioning
confidence: 99%
“…These services usually include access control provision of learning content, communication tools, and organizations of user groups. [12] The communication tools include announcements, discussion, chat, and mail. The announcements help the faculty members to post messages for students.…”
Section: Introductionmentioning
confidence: 99%
“…本研究采用定性和定量相结合的研究方式, 运用 SPSS (25.0 版本) 软件对 95 份问卷进行分析, 并结合对 12 位学生及 8 位教师的一对一访谈,对这两个平台的直播交互式汉语教学进行探讨。 本研究参考(El-Sawy, 2018)及 (Pusuluri, Mahasneh & Alsayer, 2017)的调查问卷,针对 英国成人汉语学习者这一研究对象进行调整改进(见附录一)。问卷的前 43 道题目采用里克 特五度量表计分,即"完全不赞同"计为 1 分,"不赞同"计为 2 分,"中立"计为 3 分,"赞 同"计为 4 分,"完全赞同"计为 5 分。反向计分处理过后,首先对问卷进行信度检验,通过 内部一致性检验得出,克伦巴赫 α 系数为 .826,表明问卷内部信度良好;再分别对八类因素内 部进行一致性检验,克伦巴赫 α 系数均在 0.7 以上,表明八类因素分组合理。 半结构化访谈参考 Chen, Dobinson & Kent(2020)…”
Section: 研究方法及工具unclassified